Listening extra : a resource book of multi-level skills activities. - Craven, Miles, ....- (Cambridge : University Press, 2006)
This book provides original and stimulating listening practice across a range of levels and topics. Activities are designed around authentic scenarios and help develop specific listening skills, such as listening for details, identifying emotions or listening for opinions. The recordings expose students to a variety of native and non-native accents and cover a range of genres from radio and television to academic lectures, presentations and conversational dialogues.
Keywords: Engels -- Taalgebruik; Leesbevordering